2022
DOI: 10.1080/23802359.2022.2109437
|View full text |Cite
|
Sign up to set email alerts
|

Bactris gasipaes Kunth var. gasipaes complete plastome and phylogenetic analysis

Abstract: Bactris gasipaes var. gasipaes (Arecaceae, Palmae) is an economically and socially important plant species for populations across tropical South and Central America. It has been domesticated from its wild variety, B. gasipaes var. chichagui , since pre-Columbian times. In this study, we sequenced the plastome of the cultivated variety, B. gasipaes Kunth var. gasipaes and compared it wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 39 publications
(50 reference statements)
0
1
0
Order By: Relevance
“…gasipaes and var. chichagui demonstrated that the differences between these two varieties are also visualized at the molecular level [ 21 , 22 ]. With the advances of molecular tools and new findings regarding the evolutionary processes, further studies are still required to better understand the infra-specific relationships among the landraces, as well as the revision of B. gasipaes nomenclature [ 18 ].…”
Section: Peach Palm Is a Domesticated Palm In Neotropicsmentioning
confidence: 99%
“…gasipaes and var. chichagui demonstrated that the differences between these two varieties are also visualized at the molecular level [ 21 , 22 ]. With the advances of molecular tools and new findings regarding the evolutionary processes, further studies are still required to better understand the infra-specific relationships among the landraces, as well as the revision of B. gasipaes nomenclature [ 18 ].…”
Section: Peach Palm Is a Domesticated Palm In Neotropicsmentioning
confidence: 99%